Upaya Meningkatkan Literasi dan Nilai Karakter Peserta Didik SD Negeri 1 Jatiwarno Kabupaten Karanganyar melalui Program Kampus Mengajar - Rahmawati, Yuniar Budi; Wibowo, Yunus Aris (Warta LPM, 2023)
There are 18 students at SD N 1 Jatiwarno whose reading, and writing skills are still relatively low. The ability to read and write is a basic ability that must be mastered by students when entering school and has a relationship with good character values in students. The government program currently being developed is a campus teaching program in which all Indonesian students can participate. Students have an important role in developing education in Indonesia to achieve national education goals. The part of campus students who teach can be identified through research using a step-by-step method starting from activity planning, the implementation phase, and corrective and follow-up activities. Based on this research, the results obtained are teaching participation of campus students in improving literacy skills and character values through learning in class, providing additional hours, assisting in using the AKM class application, getting used to Duha prayer, and making a place to save. Duha prayer activities are implemented at SD N 1 Jatiwarno as a daily routine to increase the value of religious character in students.